1986
DOI: 10.1159/000238410
|View full text |Cite
|
Sign up to set email alerts
|

Single-versus Multiple-Dose Mezlocillin Prophylaxis in Emergency Cesarean Section

Abstract: 163 patients undergoing emergency cesarean section were prospectively and randomized evaluated to determine the effect of mezlocillin in reducing postoperative morbidity. We compared a single 5-gram preoperative dose and a perioperative 3-dose regimen, each of 2 g, with a placebo. Postoperative morbidity was reduced from 65% in the placebo group to 20% in the groups receiving mezlocillin (p < 0.005). The incidences of febrile morbidity, endometritis and urinary tract infection were all significantly lower in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 10 publications
(12 reference statements)
0
25
0
Order By: Relevance
“…The majority of studies were set in developed countries (USA, Canada, Italy, Israel, the Netherlands), whereas only five studies were conducted in developing nations, including Nepal, Pakistan, United Arab Emirates and Tanzania.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies were set in developed countries (USA, Canada, Italy, Israel, the Netherlands), whereas only five studies were conducted in developing nations, including Nepal, Pakistan, United Arab Emirates and Tanzania.…”
Section: Resultsmentioning
confidence: 99%
“…All studies assessed the use of the same intravenous antibiotic prophylaxis, either in a single dose or a multiple dose. The majority reported the use of monotherapy, whereas three trials compared combined regimens . The classes of antibiotics addressed included penicillins, cephalosporins and aminoglycosides.…”
Section: Resultsmentioning
confidence: 99%
“…In 19 studies (N = 2229), there were data on non-elective procedures D'Angelo 1980;Elliott 1986;Gibbs 1981;Harger 1981;Hawrylyshyn 1983;Leonetti 1989;Moodley 1981;Ross 1984;Ruiz-Moreno 1991;Scarpignato 1982;Schedvins 1986;Tzingounis 1982;Weissberg 1971;Wong 1978;Work 1977;Young 1983). Three studies (N = 573) included both women having elective cesareans and non-elective cesareans (Dashow 1986;Jaffe 1984;Rothbard 1975). The remaining, and the majority of studies did not differentiate between an elective or nonelective procedure, or the definitions used were not consistent with those used in this review; these have been grouped as 'both' or 'undefined'.…”
Section: Included Studiesmentioning
confidence: 99%
“…Often a repeat section had been classified as elective by the study authors, but it was not always evident that all of these women were indeed not in labor and often the duration of membrane rupture was unclear. Fifty-two studies (N = 7765) were classified as undefined type of cesarean section (Adeleye 1981;Allen 1972;Apuzzio 1982;Bibi 1994;Bilgin 1998;Bourgeois 1985;Carl 2000;Chan 1989;De Boer 1989;Duff 1980;Engel 1984;Escobedo 1991;Gall 1979;Ganesh 1986;Gerstner 1980;Gibbs 1972;Gibbs 1973;Gordon 1979;Gummerus 1984;Hager 1983;Hagglund 1989;Ismail 1990;Jaffe 1985;Karhunen 1985;Kellum 1985;Kreutner 1978;Kristensen 1990;Lapas 1988;Levin 1983;Lewis 1990;McCowan 1980;Miller 1968;Moro 1974;Morrison 1973;Ng 1992;Padilla 1983;Phelan 1979;Polk 1982;Reckel 1985;Rehu 1980;Saltzman 1985;Stage 1982;Stiver 1983;…”
Section: Included Studiesmentioning
confidence: 99%
“…Numerous reports have shown that there is no significant difference in the incidence of postoperative urinary tract infection after Caesarean section and gynaecological surgery when a single preoperative dose of antibiotics is given compared with repeated administrations of antibiotics (5,6). In the latter part of the current series, single dose prophylaxis was often administered.…”
Section: Discussionmentioning
confidence: 93%